2018
DOI: 10.13189/ijbb.2018.060401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory Activity of Crinum scillifolium Extracts in Wistar Rats

Abstract: Aim of study: Inflammation was associated with many diseases in humans. Crinum species have a considerable medicinal reputation as potent folkloric remedies. The main objective of the study was to evaluate the anti-inflammatory activity of aqueous and hydroethanolic extracts of Crinum scillifolium bulbs in in vivo models. Materials and methods: The anti-inflammatory effect of Crinum scillifolium extracts was also evaluated in carrageenan-induced paw edema models and C-reactive protein (CRP) levels was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They would also present protective activities of veins and capillaries (Macheix and al., 2005). In addition to these compounds, alkaloids have antibiotic, antiparasitic and analgesic activities (Koua and al., 2018) and would also have an effect on the central nervous system (Bruneton and al., 2009). Finally, terpenoids and steroids derived from terpenoids constitute the largest known set of secondary plant metabolites (Yamunadevi and al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…They would also present protective activities of veins and capillaries (Macheix and al., 2005). In addition to these compounds, alkaloids have antibiotic, antiparasitic and analgesic activities (Koua and al., 2018) and would also have an effect on the central nervous system (Bruneton and al., 2009). Finally, terpenoids and steroids derived from terpenoids constitute the largest known set of secondary plant metabolites (Yamunadevi and al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, according to Allegra [24] ; Eom [25]; alkaloids are well known for their ability to inhibit pain perception. Furthermore, Koua [26], showed that the presence of flavonoids in Crinum scillifolium extracts would have inhibited acetic acid injection-induced spasms. The presence of these chemical compounds in ZHm extracts would therefore be responsible for its peripheral analgesic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the volume of rat paw edema by ZHm extracts at 400 and 800 mg/kg bw could be explained by the presence of polyphenols in these extracts. These would have acted as substances with antagonistic action on the effects of histamine, serotonin, bradykinin and prostaglandin biosynthesis [26].…”
Section: Discussionmentioning
confidence: 99%